2021
DOI: 10.1002/ange.202101033
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen Atom Transfer from HOO. to ortho‐Quinones Explains the Antioxidant Activity of Polydopamine

Abstract: Melanins are stable and non-toxic biomaterials with a great potential as chemopreventive agents for diseases connected with oxidative stress, but the mechanism of their antioxidant action is unclear. Herein, we show that polydopamine (PDA), a well-known synthetic melanin, becomes an excellent trap for alkylperoxyl radicals (ROOC, typically formed during autoxidation of lipid substrates) in the presence of hydroperoxyl radicals (HOOC). The key reaction explaining this peculiar antioxidant activity is the reduct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…A recent study, they found that the antioxidant chemistry of ortho and para ‐quinones endows PDA with redox‐mediated bioactivity. [ 35 ] It involves the trap of hydroperoxyl radicals (HOO•) to form the alkyl peroxyl radicals (ROO•) by the reduction of the ortho‐quinone moieties. Besides, the abundant hydroquinone units of the re ‐COFs skeleton could quench the H 2 O 2 /ROS in 1D channels, whereas itself was oxidated to quinone states of ox ‐COFs.…”
Section: Resultsmentioning
confidence: 99%
“…A recent study, they found that the antioxidant chemistry of ortho and para ‐quinones endows PDA with redox‐mediated bioactivity. [ 35 ] It involves the trap of hydroperoxyl radicals (HOO•) to form the alkyl peroxyl radicals (ROO•) by the reduction of the ortho‐quinone moieties. Besides, the abundant hydroquinone units of the re ‐COFs skeleton could quench the H 2 O 2 /ROS in 1D channels, whereas itself was oxidated to quinone states of ox ‐COFs.…”
Section: Resultsmentioning
confidence: 99%
“…For example, dopamine (DA) has demonstrated with potent capacity to oxidize reductive graphene, where the resultant oxidized graphene displayed excellent electroconductivity. 22 Interesting, there are many factors for regulating the ROS scavenging property of polyphenolic platforms, such as phenolic hydroxyl group position and number, 69,70 polyphenol type, 71 size, and microstructure of polyphenolic platforms. 72,73 For example, our group has uncovered that the doped arginine into the microstructure of polydopamine (PDA) particles could destroy the compact p-stacked microstructures within PDA, resulting in antioxidant property enhancement.…”
Section: Non-covalent Interactionsmentioning
confidence: 99%
“…Copyright 2020, Elsevier. (C) Radical reactions between dopamine and typical free radicals (ROO•, HOO•) 115 …”
Section: Fire‐retardant Polymeric Nanocomposites Through Fighting Fre...mentioning
confidence: 99%
“…The proposed reaction mechanism between dopamine and typical free radicals (ROO•, HOO•) is provided in Figure 10C. 115 In addition to the intrinsic fire-resistant polymers, dopamine derivatives can be used alone or in combination with other FRs to prepare flame-retardant coatings for cellulose, 116 PU, [117][118][119] EP, 120 and UHMWPE. 121 These studies have further highlighted that it is the freeradical scavenging effect and a good charring capability of dopamine-derived molecules (e.g., catechol units) that are responsible for the excellent fire retardancy of the coatings.…”
Section: Dopamine and Its Derivativesmentioning
confidence: 99%
See 1 more Smart Citation